Modelado estadístico del efecto de burbujas de aire en sistemas de comunicaciones ópticos inalámbricos submarinos. - Gómez-García, Carlos; Iamaguti-Debessa, Jacqueline; Salcedo-Serrano, Pedro; Boluda-Ruiz, Rubén; Garrido-Balsells, José María; García-Zambrana, Antonio; Puerta-Notario, Antonio; Puerta-Notario (My University, 2023)
The studies regarding underwater optical communications require an in-deep characterization of the water itself since its properties of absorption and scattering of light affect the transmission in an optical link. That said, this paper presents the modeling and characterization of the statistical behavior regarding the scattering caused by air bubbles of different sizes in an underwater optical wireless channel. It also provides the best statistical fitting according to each case in which a bimodal statistical form was discovered for a large-size air bubbles matter. Furthermore, it explains how all the assembly and installation are made at the laboratory in order to achieve the results obtained. It also features an audio interface as an easy way to get data variations.
Keywords: Comunicaciones ópticas; Análisis multivariante; Comunicaciones ópticas inalámbricas submarinas; Modelado estadístico; Trabajo experimental